2007
DOI: 10.1021/cg0700061
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of InxGa1–xAs and GaAs1–yPy Layers Surrounding the AlAs Release Layer in the Epitaxial Lift-Off Process

Abstract: In this paper, the influence of intrinsic strain on the epitaxial lift-off (ELO) process induced by local lattice mismatch is determined as a function of the composition variation of two In x Ga1–x As or two GaAs1–y P y layers surrounding the AlAs etch layer. For this purpose, samples were grown by metal organic chemical vapor deposition, etched using a weight-induced ELO process, and analyzed by differential interference contrast microscopy and atomic force microscopy. It is shown that the etch rate decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 42 publications
2
8
0
Order By: Relevance
“…At this composition the AlAs 1−y P y layer is almost lattice matched with the surrounding GaAs layers, thus it can be concluded that the maximum etch rate is obtained for an almost unstrained release layer. This correlates well with the fact that in previous work 13 it was observed that the ELO etch rate maximizes for layer structures with the least amount of strain in the two In x Ga 1−x As or two GaAs 1−y P y layers surrounding the AlAs release layer. This dependence of the lateral etch rate on the strain in the release layer structure is a strong indication that under these conditions the ELO process is hampered by reaction rate limitations.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…At this composition the AlAs 1−y P y layer is almost lattice matched with the surrounding GaAs layers, thus it can be concluded that the maximum etch rate is obtained for an almost unstrained release layer. This correlates well with the fact that in previous work 13 it was observed that the ELO etch rate maximizes for layer structures with the least amount of strain in the two In x Ga 1−x As or two GaAs 1−y P y layers surrounding the AlAs release layer. This dependence of the lateral etch rate on the strain in the release layer structure is a strong indication that under these conditions the ELO process is hampered by reaction rate limitations.…”
Section: Discussionsupporting
confidence: 91%
“…In the actual experiments, however, much larger etch rates of several mm/h were obtained. [11][12][13] Nevertheless, the experiments 11 did show qualitatively the predicted linear relation between V e and h −0.5 , indicating that at least under some conditions diffusion does play a limiting role in the etch process. On the other hand, there is also experimental evidence that points to a reaction rate related process.…”
mentioning
confidence: 90%
See 3 more Smart Citations